2012
DOI: 10.1371/journal.pone.0049273
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Germination of Orobanche cumana Seeds in the Presence of Arbuscular Mycorrhizal Fungi or Their Exudates

Abstract: Broomrapes (Orobanche and Phelipanche spp) are parasitic plants responsible for important crop losses, and efficient procedures to control these pests are scarce. Biological control is one of the possible strategies to tackle these pests. Arbuscular Mycorrhizal (AM) fungi are widespread soil microorganisms that live symbiotically with the roots of most plant species, and they have already been tested on sorghum for their ability to reduce infestation by witchweeds, another kind of parasitic plants. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 43 publications
1
30
0
2
Order By: Relevance
“…Inoculum from one organic farm completely prevented seed germination, demonstrating that this pattern could be important in some agricultural settings. We are unaware of a mechanism that could explain these results, although a recent report that AMF spore exudates suppress seed germination of a parasitic plant (Louarn et al 2012) suggests further studies of this phenomenon are warranted.…”
Section: Direct Effectsmentioning
confidence: 99%
“…Inoculum from one organic farm completely prevented seed germination, demonstrating that this pattern could be important in some agricultural settings. We are unaware of a mechanism that could explain these results, although a recent report that AMF spore exudates suppress seed germination of a parasitic plant (Louarn et al 2012) suggests further studies of this phenomenon are warranted.…”
Section: Direct Effectsmentioning
confidence: 99%
“…Researchers also tried to eliminate Orobanche aegyptiaca through different methods mainly including hand weeding, adjustment of the sowing dates of main crops, application of chemical herbicides and biological herbicides, selection and breeding of Orobanche-resistant crop cultivars and elimination of the Orobanche seed bank in soil based on crop induction, etc., (Parker and Riches 1993;Dhanapal, et al, 1996;Louarn, et al, 2012;Ma, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some degree of reduction germination of O. cumana Wallr., seeds in the presence of AMF and their exudates have been found. Besides a lower production of germination stimulants was also marked antagonism between the AMF and the parasite (Louarn, 2012). The most recent research has shown that not only strigolactones stimulate the germination of seeds of broomrapes, but a several substances of other classes metabolites have been identified (Cordozo et al, 2011;FernandezAparicio et al, 2011;Raupp et al, 2013).…”
Section: Issn: 2319-7706 Volume 6 Number 1 (2017) Pp 733-746mentioning
confidence: 99%